Generalized Quasilikelihood Inference for Zero Inflated Longitudinal Count Data - Antu, Jannatul Ferdous; Sharmin, Sabina; Mallick, Taslim Sazzad (Dhaka University Journal of Science, 2020)
In this paper, we extend an observation-driven model for time series of zero inflated count data to longitudinal data setup. Basic properties of the models are discussed. For statistical inference of the proposed model, a generalized quasilikelihood (GQL) estimating equation has been derived for the regression parameter. A pharmaceutical data has been reanalyzed using the proposed approach and results are compared. The proposed approach produces similar estimates as given in the earlier work with much smaller standard errors. Dhaka Univ. J. Sci. 68(1): 95-99, 2020 (January)